DAMONTE, Gerardo H. The Constitution of Political Actors. Peasant Communities, Mining, and Mobilization in Bolivian and Peruvian Andes. Saarbrücken-Berlin: VDM Verlag, 2008, 349 pp. - Bravo Frey, Mireya (2010)
La reseña no presenta resumen.